Aspergillus niger PA2 Tyrosinase Covalently Immobilized on a Novel Eco-Friendly Bio-Composite of Chitosan-Gelatin and Its Evaluation for L-DOPA Production - Agarwal, Pragati; Dubey, Swati; Singh, Mukta; Singh, Rajesh P. (Frontiers in Microbiology, 2016)
Tyrosinase (EC 1.14.18.1) a copper-containing monooxygenase, isolated from a fungal isolate Aspergillus niger PA2 was subjected for immobilization onto a composite consisting of chitosan and gelatin biopolymers. The homogeneity of the chitosan-gelatin biocomposite film was characterized by X-ray diffraction analyses. To evaluate immobilization efficiency, chitosan-gelatin-Tyr bio-composite films were analyzed by field emission scanning electron microscopy, atomic force microscopy and UV-spectroscopy. The rough morphology of the film led to a high loading of enzyme and it could retain its bioactivity for a longer period. The enzyme adsorbed onto the film exhibited 72% of its activity after 10 days and exhibited good repeatability for up to nine times, after intermittent storage. Moreover, the immobilized enzyme exhibited broader pH and temperature profile as compared to free counterpart. Immobilized enzyme was further evaluated for the synthesis of L-DOPA (2,4-dihydroxy phenylalanine) which is a precursor of dopamine and a potent drug for the treatment of Parkinson’s disease and for myocardium neurogenic injury.